Electromagnetic Fields and Waves 2019
DOI: 10.5772/intechopen.84704
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Electromagnetic Field on the Development of Chick Embryo: An In Vivo Study

Abstract: This study was conducted to explore the effects of electromagnetic waves on a developing chick embryo. The radiofrequency electromagnetic waves (RFW) emitted by different smart phones was measured by using a TriField meter. Chick fertilized eggs were placed in an egg incubator, divided into control and exposed groups. In the exposed group, a mobile phone was placed inside an incubator in call receiving mode, while in the control group, the mobile phone was not used. Studies were conducted at low and high expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 42 publications
(49 reference statements)
0
7
0
Order By: Relevance
“…The most obvious finding from this study was that the hatching rate was 15% in both sham and treated groups, while it was 100% in the control group. A study reported that the exposed groups to 1800 MHz EMR for100-200 minutes revealed no mortality at all, while at longer exposure for 500-750 minutes raised the mortality rate to 14% [17]. Higher mortality rate was also noticed by another study in the exposed group [18].…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…The most obvious finding from this study was that the hatching rate was 15% in both sham and treated groups, while it was 100% in the control group. A study reported that the exposed groups to 1800 MHz EMR for100-200 minutes revealed no mortality at all, while at longer exposure for 500-750 minutes raised the mortality rate to 14% [17]. Higher mortality rate was also noticed by another study in the exposed group [18].…”
Section: Discussionmentioning
confidence: 81%
“…These processes could be affected by endogenous ionic flows and electric fields which could be disturbed by the EMR exposure. Growth retardation in the exposed group is most likely due to the adverse effects of EMR on the DNA [17].…”
Section: Discussionmentioning
confidence: 99%
“…The incubated eggs of the controls and treated groups were steadily checked for viability and mortality by using the candling technique. Dead embryos were delicately removed from the yolk sac, cleaned with saline, checked for any obvious malformations, and then classified in accordance with [19,20]. Dead embryos were determined by the absence of beating heart, no distinguishable vasculature, or the presence of blood spots.…”
Section: Morphological Investigation and Measurementsmentioning
confidence: 99%
“…Low-frequency electromagnetic fields can affect cell growth (7), morphology and cell shape (8), carcinogenicity (9), cell differentiation (10), and programmed cell death (11). Exposure to lowfrequency electromagnetic fields could increase oxidative stress in chick embryos (12), cultured mammalian cells (13), and human erythrocytes (14). Gastric cancer is a multifactorial disease in which bacterial contamination, environmental factors, and host genetic agents play an important role in its progression (15).…”
Section: Introductionmentioning
confidence: 99%